2016
DOI: 10.3892/mmr.2016.5705
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the availability of iron during hypoxia on the genes associated with apoptotic activity and local iron metabolism in rat H9C2 cardiomyocytes and L6G8C5 skeletal myocytes

Abstract: The differential availability of iron during hypoxia is presumed to affect the functioning of cardiac and skeletal myocytes. Rat H9C2 cardiomyocytes and L6G8C5 myocytes were cultured for 48 h in normoxic or hypoxic conditions at the optimal, reduced or increased iron concentration. The mRNA expression levels of markers of apoptosis [B‑cell lymphoma‑2 (Bcl2; inhibition) and Bcl‑2‑activated X protein (Bax; induction)], atrophy (Atrogin), glycolysis (pyruvate kinase 2; PKM2) and iron metabolism [transferrin recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 52 publications
1
19
0
2
Order By: Relevance
“…It may be hypothesized that the disturbed iron metabolism observed in HF affects skeletal muscles, which leads to their dysfunction and exercise intolerance. The present authors have recently demonstrated that, during hypoxia, reduced iron concentration had a greater negative impact on the viability and functioning of myocytes, compared with augmented iron availability ( 24 ).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It may be hypothesized that the disturbed iron metabolism observed in HF affects skeletal muscles, which leads to their dysfunction and exercise intolerance. The present authors have recently demonstrated that, during hypoxia, reduced iron concentration had a greater negative impact on the viability and functioning of myocytes, compared with augmented iron availability ( 24 ).…”
Section: Introductionmentioning
confidence: 83%
“…Rat L6G8C5 skeletal myocytes (L6; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) were cultured in normoxia (18% O 2 , 5% CO 2 ) or hypoxia (1% O 2 , 5% CO 2 , 94% N 2 ), for 48 h ( 24 ), supplemented with 100 µ M deferoxamine (DFO; Sigma-Aldrich; Merck KGaA) or 200 µ M ammonium ferric citrate (AFC; Sigma-Aldrich; Merck KGaA) in order to change iron accessibility ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three main issues that need to be considered in relation to the ACS pathophysiology. First, accumulated experimental data clearly show that during hypoxic conditions, mainly caused by underlying ischaemic disease, iron impairs the viability of cardiomyocytes [ 20 ]. Iron seems to act as a protective agent, since the levels of cellular atrophy decreases in hypoxic rat cardiomyocytes treated with iron salt [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might enhance ischemic stress and apoptosis of cardiomyocytes [ 32 ]. Moreover, experimental data clearly show that during hypoxic conditions, mainly caused by underlying ischaemic disease, iron deficiency impairs the viability of cardiomyocytes [ 33 ]. In contrast, the availability of iron during hypoxic conditions is beneficial on genes associated with apoptotic activity in rat cardiomyocytes and also on skeletal myocytes.…”
Section: Discussionmentioning
confidence: 99%